2012
DOI: 10.1136/bmjopen-2012-001600
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of haematological parameters in HIV-infected and uninfected Rwandan women: a cross-sectional study

Abstract: ObjectivesAlthough haematological abnormalities are common manifestations of HIV infection, few studies on haematological parameters in HIV-infected persons have been undertaken in sub-Saharan Africa. The authors assessed factors associated with haematological parameters in HIV-infected antiretroviral-naïve and HIV-uninfected Rwandan women.Study designCross-sectional analysis of a longitudinal cohort.SettingCommunity-based women's associations.Participants710 HIV-infected (HIV+) antiretroviral-naïve and 226 HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 32 publications
11
52
3
Order By: Relevance
“…[6,7] With regard to other studies conducted among South Africans, the prevalence of anaemia among ART-naive patients was similar to that reported by Kerkhoff et al, [10] (~70%), but higher than that documented by Takuva et al [11] and Firnhaber et al, [5] who both reported anaemia (Hb <10 g/dL) in ~20 -25% of patients (as opposed to ~40% with Hb concentrations in this range in our study). The generally higher anaemia prevalence observed in this study compared with the majority of other African cohorts may be attributable to the fact that many of the previous studies in this field were performed in patients who were either enrolled in clinical trials or seen at outpatient ART clinics.…”
Section: Researchsupporting
confidence: 89%
See 2 more Smart Citations
“…[6,7] With regard to other studies conducted among South Africans, the prevalence of anaemia among ART-naive patients was similar to that reported by Kerkhoff et al, [10] (~70%), but higher than that documented by Takuva et al [11] and Firnhaber et al, [5] who both reported anaemia (Hb <10 g/dL) in ~20 -25% of patients (as opposed to ~40% with Hb concentrations in this range in our study). The generally higher anaemia prevalence observed in this study compared with the majority of other African cohorts may be attributable to the fact that many of the previous studies in this field were performed in patients who were either enrolled in clinical trials or seen at outpatient ART clinics.…”
Section: Researchsupporting
confidence: 89%
“…The impact on haematology services is singularly notable because of the numerous haematological complications of HIV infection, which occur secondary to effects of the virus itself, as a result of associated opportunistic infections/malignancies, or as adverse drug effects. [1] Several studies have reported the prevalence of haematological complications in HIV-seropositive patients, [2][3][4][5][6][7] with variables such as disease stage and exposure to antiretroviral therapy (ART) being important determinants. [8] However, there is a paucity of published SA data in this regard, despite the fact that the burden of HIV infection in SA is among the highest in the world.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed a significant decrease (p < 0.05) in platelet count in HIV HAART naïve patients when compared to HIV HAART patients and controls. This is in agreement with the works of Munyazesa et al 36 and Vannappagari et al 41 who reported higher prevalence of thrombocytopenia in HIV-infected individuals. The marked reduction in platelet counts may directly be attributed to the ability of HIV to directly suppress platelet production by infecting megakaryocytes and indirectly suppress production by causing alterations in the production of cytokines (cell-produced chemicals) and growth factors needed for proper platelet production and function.…”
Section: Cd4 Counts and Some Haematological Parameters Of Hiv Positivsupporting
confidence: 83%
“…Among these hematologic disorders, anemia is the most common hematologic manifestation (2,4,5). In different studies, the prevalence of anemia in individuals with AIDS has been reported at 63% to 95%, making it more common than thrombocytopenia or leukopenia in AIDS patients (6).…”
Section: Introductionmentioning
confidence: 99%